1997
DOI: 10.1109/61.584359
|View full text |Cite
|
Sign up to set email alerts
|

Controlled closing on shunt reactor compensated transmission lines. I. Closing control device development

Abstract: A control device for point-on-wave closing or autoreclosing of shunt reactor compensated transmission lines for reduction of closing overvoltages is presented. The device is the first of its kind. It was put into field service successfully more than a year ago. Development aspects and basic investigations on the relevant transient switching phenomena are presented. The algorithm employed works independently of the shape of the voltage signal to be synchronized on by means of pattern recognition. Peculiarities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 2 publications
0
13
0
5
Order By: Relevance
“…That is the case reported in [4], where the design optimisation of the 550 kV, 330 km long line imposes severe limits for line switching overvoltages (1.7 pu). Controlled switching has been applied to different switching conditions in HV networks for about 10 years.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…That is the case reported in [4], where the design optimisation of the 550 kV, 330 km long line imposes severe limits for line switching overvoltages (1.7 pu). Controlled switching has been applied to different switching conditions in HV networks for about 10 years.…”
Section: Discussionmentioning
confidence: 92%
“…However, satisfactory technological solutions to put in practice the idea could only be developed in more recent times, thanks to the evolution of high-voltage circuit breaker designs and to the development of micro-electronic devices applied to power systems. The recently -reported experiences of the use of synchronous-switching systems have shown that these devices can be very efficient to control switching overvoltages, having thus become a powerful means at the disposition of utilities to help them meet stringent insulation coordination requirements, such as those generally especified when compact lines are to be used [4] . Accordingly, in the present study this solution has also been investigated, as a possible alternative to the use of closing resistors, generally quite onerous for EHV circuit breakers.…”
Section: Synchronizersmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of the rate of decrease of dielectric strength should exceed the maximum derivative of the applied voltage for proper operation of CB. The maximum pre-striking voltage is determined according to the statistical scatter of the contact's speed [6].…”
Section: Introductionmentioning
confidence: 99%
“…The value of the rate of decrease of dielectric strength should exceed the maximum derivative of the applied voltage for 14 proper operation of CB. The maximum pre-striking voltage is determined according to the statistical scatter of the contact's speed [6].…”
Section: Introductionmentioning
confidence: 99%